2020
DOI: 10.1371/journal.pone.0234477
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grazing on the allocation of mass of soil aggregates and aggregate-associated organic carbon in an alpine meadow

Abstract: Soil aggregation is closely related to the soil organic carbon sequestration, both of which plays an important role in the stability of the soil carbon pool. However, the results of the impact of yak grazing intensity on the soil carbon process in alpine meadows have been unclear. With the marsh meadow as the research object in the Gahai wetland of the east Qinghai-Tibet Plateau, we analyzed the influence of different grazing intensities on the allocation of mass, stability and aggregate-associated organic car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…As a result, medium and high grazing offset the increased aggregates stimulated by grazing. Our result is consistent with Wang et al (2020) who also found light grazing promoted the formation of coarse aggregates and higher grazing intensity caused the disintegration of soil aggregates. Our results also showed that coarse aggregate stability was lower than fine aggregate stability (Figures 3B,E, Figures 4B,E).…”
Section: Effect Of Rotational Grazing On Grassland Soilsupporting
confidence: 93%
“…As a result, medium and high grazing offset the increased aggregates stimulated by grazing. Our result is consistent with Wang et al (2020) who also found light grazing promoted the formation of coarse aggregates and higher grazing intensity caused the disintegration of soil aggregates. Our results also showed that coarse aggregate stability was lower than fine aggregate stability (Figures 3B,E, Figures 4B,E).…”
Section: Effect Of Rotational Grazing On Grassland Soilsupporting
confidence: 93%
“…Studies of the impact of animal trampling on haphazardly used pastures have shown that the harmful effects of animal grazing on volume density and aggregate stability tend to become more serious as the number of animals grazing per unit area increases [Poffenbarger, 2010;Wang et al, 2020]. We found an increase in soil compaction of up to 13.11% with an increase in grazing intensity compared to no grazing [Neff et al, 2005].…”
Section: Soil Indicatorsmentioning
confidence: 58%
“…Soil microorganisms are the living components in the soil, which are extremely sensitive to various changes in the soil environment and can fully re ect the ecological functions of microbial communities. Microbial biomass is not only an important source of soil nutrients, but also an important carrier for soil nutrient xation (Wang et al, 2020). Soil MBC is an active component of the soil carbon pool and plays an important role in the soil carbon cycle (Lihua et al, 2010).…”
Section: Effects Of Betula Platyphylla Invasion On Soil Organic Carbo...mentioning
confidence: 99%